Wear behaviour of PN+CrN, PN+CrAlN and PN+TiCrAlN layer composite during ball-on-disk tests in higher temperature - Kacprzynska, Joanna; Smolik, Jerzy; Mazurkiewicz, Adam (International Conference on Plasma Surface Engineering, 2013)
Not available